(untitled) (Castilla. Estudios de Literatura, 2020)
Las palabras a los reyes y gloria de los Pizarros is a comedia by Luis Vélez de Guevara, in which this playwright of the Spanish Golden Age represents the conquest of Peru by the brothers Francisco and Hernando Pizarro. This article does a segmentation of the play following Marc Vitse’s proposal. This way the play’s three acts are divided into macro and microsequences according to the metric change and the relationship of the obtained segments is examined.